(untitled) (Journal of the College of Basic Education, 2022)
This study was conducted in Amman Primary School for Boys located in Diyala Governorate / Baquba, and aimed to know the impact of Hilda Taba’s model on the collection of grammatical concepts among primary school students.The research sample consisted of 54 students, including (27) a student studying Arabic grammar using the Hilda Tapa model and (27) a student studying grammar in the traditional way. At the beginning of the academic year 2013-2014 and it lasted a full semester, and at the end of the experiment, the researcher conducted a post-achievement test for both groups, and the results showed that there was a statistically significant difference at the level (0.05) in favor of the experimental group.